The Influence of Motivation, Competence, and Work Environment on Employee Performance through Job Satisfaction as an Intervening Variable at the Ministry of Investment / BKPM (Badan Koordinasi Penanaman Modal) of the Republic of Indonesia in 2023 - Amallia, Shoffi; Krisnandi, Herry (Budapest International Research and Critics University, 2024)
Researchers took the title The Influence Of Motivation, Competence, and Work Environment On Employee Performance Through Job Satisfaction As An Intervening Variable At The Ministry Of Investment / BKPM (Badan Koordinasi Penanaman Modal) Of The Republic Of Indonesia. The sample size was 126 respondents. The analysis method used is quantitative using SEM. The results showed 1) Motivation and Competence have a positive and significant effect on Job Satisfaction; 2) Work Environment has a positive and insignificant effect on Job Satisfaction; 3) Motivation and Competence have a positive and significant effect on Employee Performance; 4) Work Environment has a positive and insignificant effect on Employee Performance; 5) Motivation, Competence and Work Environment have an insignificant effect on employee performance through job satisfaction; 6) Job Satisfaction has a positive and insignificant effect on Employee Performance.